Exploring Teachers' Narratives: Challenges and Strategies for Enhancing the Teaching Process - Dursun, Fevzi; Aykan, Ahmet (Sage Publications Inc, 2025)
The aim of this study is to examine teachers' perspectives on enhancing the efficiency of the teaching process and to identify the challenges they face while offering potential solutions. The research was conducted using a qualitative narrative inquiry design to explore teachers' experiences and perspectives deeply. The study group consists of 57 volunteer teachers reached through snowball sampling. A semi-structured interview form was used as the data collection tool to gain a comprehensive understanding of teachers' views. The data were analyzed through content analysis. The findings reveal that an effective teaching process is based on elements such as planning and preparation, active student participation, the organization of the learning environment, and the diversity of teaching methods and techniques used. Factors negatively affecting the teaching process include student-related issues, physical deficiencies, low teacher motivation, an intensive curriculum, and insufficient parental support. As a result, it is recommended that teacher professional development should be supported, classroom environments should be better organized, and stronger cooperation with school administrators should be promoted to improve the teaching process. Additionally, making the curriculum more flexible and increasing the application of student-centered methods could enhance the efficiency of the process. The study suggests future research on the relationship between the physical conditions of educational environments and teaching efficiency, the impact of different teaching methods on student achievement, and how teachers' motivation levels influence the teaching process.
Keywords: teachers' efforts; teaching process; quality-efficiency in teaching